A critical approach to Pastime Park (1893-1914) as an exhibitionary and dreamworld complex. Issue 2 (26th May 2020) - Rodríguez-Granell, Ana
Abstract : This article seeks to analyse the Parque del Pasatiempos (Pastime Park) complex (1893–1914) located in the city of Betanzos, in north-western Spain. As an architectural and sculptural complex, the space provides an interesting case for studying the cultural history of the turn of the 19th and 20th centuries and the emergence of museum and recreational complexes. The aim is to contextualise the Park's specificity in light of the colonial dynamics of the north of Spain, and also, through visual studies literature, establish the connection between the complex and an entire range of practices and artefacts that existed, both in Spain and internationally, at the end of the 19th century, such as world expositions, public parks and amusement parks. Through this constellation of meaning, we shall try to understand how these exhibitionary complexes have a place within the tensions inherent in enlightened dialectics, between discipline and instruction and the release of bodies.